Upregulation of CRISP3 and its clinical values in adult sepsis: a comprehensive analysis based on microarrays and a two-retrospective-cohort study - Zhang, An-qiang; Wen, Da-lin; Ma, Xin-xin; Zhang, Fei; Chen, Guo-sheng; Maimaiti, Kelimu; Xu, Gang (Frontiers in Immunology, 2024)
BackgroundCurrent lines of evidence indicate that cysteine-rich secretory protein 3 (CRISP3) is an immunoregulatory factor. Nevertheless, no study has explored the relationships between the values of CRISP3 and sepsis.MethodsWe conducted a comprehensive literature search and meta-analysis from the Gene Expression Omnibus (GEO) and ArrayExpress to determine the expression of CRISP3 in sepsis patients. Then, we explored whether plasma CRISP3 could serve as a potential biomarker to predict the risk of sepsis via two retrospective trauma cohorts. We evaluated the prediction power using the area under the curve (AUC).ResultsA total of 23 datasets were recruited for the comprehensive meta-analysis, and the combined standardized mean difference (SMD) of CRISP3 was 0.90 (0.50–1.30) (p < 0.001), suggesting that CRISP3 was overexpressed in sepsis patients. Meanwhile, sepsis patients had higher CRISP3 concentrations than non-sepsis patients in 54 trauma patients (p < 0.001). Plasma CRISP3 on admission was significantly associated with the incidence of sepsis [OR = 1.004 (1.002–1.006), p < 0.001]. As a predictive biomarker, CRISP3 obtained a better AUC [0.811 (0.681–0.905)] than C-reactive protein (CRP) [0.605 (0.463–0.735)], procalcitonin (PCT) [0.554 (0.412–0.689)], and Sequential Organ Failure Assessment (SOFA) [0.754 (0.618–0.861)]. Additionally, the clinical relationships between plasma CRISP3 and sepsis were verified in another trauma cohort with 166 patients [OR = 1.002 (1.001–1.003), p < 0.001]. The AUC of CRISP3 was 0.772 (0.701–0.834), which was better than that of CRP [0.521 (0.442–0.599)] and PCT [0.531 (0.452–0.609)], but not SOFA [0.791 (0.717–0.853)].ConclusionOur study indicated and validated that CRISP3 was highly expressed in sepsis. More importantly, CRISP3 may serve as a latent biomarker to predict the risk of sepsis.